Kinetic and Thermodynamic Analysis of Thermal Decomposition of Waste Virgin PE and Waste Recycled PE - Nurameylia Rasaidi; Ahmad Rafizan Mohamad Daud; Siti Norazian Ismail (International Journal of Renewable Energy Development, 2022)
Polyethylene is one of the key components of plastic wastes that can be utilized for resource recovery through pyrolysis method. Understanding of thermal decomposition properties and reaction mechanism of pyrolysis are necessary in designing an efficient reactor system. This study investigated the kinetics and thermodynamics parameters for individual waste virgin polyethylene (WVPE) and waste recycled polyethylene (WRPE) by using distributed activation energy model (DAEM). The calculated kinetic parameters (activation energy (Ea) and pre-exponential factor (A) were used to determine thermodynamic parameters (enthalpy (ΔH), Gibbs free energy (ΔG) and entropy (ΔS). The activation energy (Ea) values for the WVPE estimated at conversion interval of 5%-95% were in the range of 180.62 to 268.04 kJ/mol while for the WRPE, the values were between 125.58 to 243.08 kJ/mol. This indicates the influence of exposure to weathering and mechanical stress during recycling on the course of the WRPE degradation. It was also found that the pyrolysis reaction for both WVPE and WRPE were best fitted using the two-dimensional diffusion (D2) model. The WVPE exhibited higher enthalpy and lower ΔG compared to WRPE, suggesting that less energy is required to thermally degrade recycled waste PE into products of char, gases and pyro-oils.  Both kinetics and thermodynamics analyses were useful for the development of the plastic waste management through pyrolysis process.